Simbol Cinta Manusia dalam Novel Zuhūr Taʾkuluhā Al-Nār Karya Amir Tag Elsir : (Semiotika Charles Sanders Pierce) - Nurhitjah Rambe; Maman Abdul Jalil; Wildan Taufiq (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Love is an inseparable part of human life, because humans will always need love in any case to continue life, because love is human nature. The intensity of love felt will vary, depending on the person who feels it and to whom the love is. Functions as a source of positive energy but can also cause bad things if misunderstood. This research aims to understand the semiosis of love symbols in the novel